Computational linguistics between reality and hope. Sebha University as a model. (Journal of Human Sciences, 2023)
In recent decades, linguistics has achieved a knowledge shift, represented by its theorists' awareness of the importance of the linguistic dimension in various fields, both human and applied. It was also represented in diagnosing problems related to applied linguistic studies, and trying to find knowledge solutions to them. Linguistic research methods have evolved as a result of changing linguistic views on the one hand, and the urgent knowledge needs of science, or the development of social needs that the world has witnessed in recent decades on the other hand, which are best represented by: technological developments, and the developments of artificial intelligence, about which views have become very intertwined today. Based on the foregoing, this paper aims to try to address the delay in research in computational linguistics, where the relationship between linguistics and the branches of natural sciences represented in: computer, that relationship that has become very important in the study of languages, including the Arabic language, will be dealt with. It has become one of the requirements for scientific progress in all branches of knowledge without exception, in addition to providing a great service to the Arabic language, especially in the field of machine translation. This will be done through two main points: the relationship between linguistics and computer science, and the reality of computational linguistics in Libyan universities, Sebha University as a model. As for the problematic of the study, it is represented in the following questions: How did the different methodological visions reflect on this scientific branch? What are the proposed solutions? What is the reality of computational linguistics in Libya? What are the desired prospects from this scientific branch? What is the impact of this on development?